Farrar Copper Spine House, floor plan, sheet no. 3 - Mark Mills::::::::: (1968)
House for Mr. & Mrs. Philip Farrar + A Proposed Addition Electrical Work: examine the electrical service & wiring of the existing servants quarters. Make the necessary changes to provide for the added electrical requirements of new construction and as required by local electrical code. Size of conductors shall be such that drop in potential under quarters. Consult with architect before locating meter, main switch box, circuit panel, outlets & switches. Th car-arborium entrance door shall have an electrically operated latch with control button at bed side and in kitchen, in addition the door shall have the usual keyed latch hardware plus a bell button with operated manually. Car Door Heating: 220 Volt baseboard & wall radiant glass heaters